The Challenges of Teaching About the Black Lives Matter Movement: A Dialogue - Troka, Donna; Adedoja, Dorcas (Radical Teacher, 2016)
This essay is a conversation between and teacher and student who worked together on the first iteration of a course that juxtaposes the Civil Rights Movement with the Black Lives Matter movement. Through their conversation they uncover what went well and what changes need to be made so that the course can be more transformative.